The Management of Expertises in Plato‘s Statesman - Bartninkas, Vilius (Literatūra, 2014)
This paper deals with the role of expertise (technē) in Plato’s Statesman. We argue that expertise is one of the central notions in the dialogue, which pervades the conception of political action and human condition in general. In the Statesman, humans are understood as technological animals whose being is in the constant state of conflict. However, the expertises do not overcome the political conflict but stimulate it even more by competing for political power. One of the activities of statesmanship is to manage and control the conflict of expertises by ordering their functions, using them for communal good and regulating them by means of disciplinary expertises. In such a way, statesmanship reveals as an expertise itself. The foundation for statesman’s expertise is his theoretical knowledge, which gives the understanding about the evolvement of the conflict of expertises and about the solutions required for political action.